2013
DOI: 10.1007/s10103-013-1290-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fractional CO2 laser irradiation on remineralization of enamel white spot lesions

Abstract: This study investigated the combined effect of fractional CO(2) laser irradiation and fluoride on treatment of enamel caries. Sixty intact premolars were randomly assigned into four groups and then stored in a demineralizing solution to induce white spot lesions. Tooth color was determined at baseline (T1) and after demineralization (T2). Afterwards, the teeth in group 1 remained untreated (control), while group 2 was exposed to an acidulated phosphate fluoride (APF) gel for 4 min. In groups 3 and 4, a fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 30 publications
6
32
1
1
Order By: Relevance
“…Todd et al 38 reported that fluoride varnish caused 50% decrease in demineralization. They used polarized microscope 28 In the present study, laser group had more microhardness values than the control but it was not significantly different. In the study of Steiner-Oliveira in 2010, using laser alone could not prevent enamel or dentin erosion.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Todd et al 38 reported that fluoride varnish caused 50% decrease in demineralization. They used polarized microscope 28 In the present study, laser group had more microhardness values than the control but it was not significantly different. In the study of Steiner-Oliveira in 2010, using laser alone could not prevent enamel or dentin erosion.…”
Section: Discussioncontrasting
confidence: 41%
“…They seem to have a synergistic effect on each other. 28 According to the present study when fluoride is applied on the enamel and then laser irradiate through it, microhardness of enamel increases significantly compared with the control. It is reported that laser increased fluoride uptake.…”
Section: Discussionmentioning
confidence: 54%
“…These areas are also defined as incipient or enamel caries. WSLs are the precursors for caries cavities and their milky color may cause esthetic problems that sometimes remain for several years later (1,2). Different options have been suggested for treatment of WSLs; some of them are conservative such as remineralization therapy; and others to some part aggressive such as bleaching or microabrasion (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that laser irradiation can enhance the resistance of tooth structure against caries formation and progression through different mechanisms. [3][4][5][6] Although various lasers have been employed for the purpose of caries prevention, erbium family lasers including Erbium-Doped Yttrium Aluminum Garnet, (Er:YAG) and Erbium, Chromium-Doped Yttrium Scandium Gallium Garnet (Er,Cr:YSGG) are the only ones that can be employed for removing dentin and enamel structures. [7][8][9] Cavity preparation by the Er:YAG laser provides advantages such as low noise and vibration, and less pain and stress for the patients, but it is more expensive and time-consuming than the conventional technique with rotary instruments.…”
Section: Introductionmentioning
confidence: 99%